Highly efficient assessment and selective determination of pancreatic cancer biomarker CA-19-9 using co-electrodeposited MXene-AgNPs nanocomposite - Mahsa Mirzayi; Balal Khalilzadeh; Sattar Akbari Nakhjavani; Rahim Mohammad-Rezaei (Sensing and Bio-Sensing Research)
An ultrasensitive and label-free electrochemical immunosensor based on MXene-AgNPs nanocomposite is reported for pancreas cancer diagnostics. Ease of deposition, high speed, thickness of deposition and high efficiency of these biosensors are their special and fundamental advantages.For this purpose, a pencil graphite electrode (PGE) was modified by silver and MXene (Ti3C2Tx (to increase efficiency and also the active surface area of PGE. Deposition of AgNPs-MXene nanocomposite then immobilization of streptavidin and biotinylated antibody on the electrode increases the sensitivity, conductivity and stability of the designed immunosensor. The electrochemical measurements in the attendance and absence of AgNPs-MXene can causing an increase in electrical currents. To examine the morphology of the developed immunosensor for the purpose of enhancing its optimal performance, the characterization methods employed include Field Emission Scanning Electron Microscopy (FE-SEM), Fourier-Transform Infrared Spectroscopy (FT-IR), and X-ray Diffraction (XRD). The results of the studies projected antibody (Ab) CA-19-9/AgNPs-MXene electrochemical immunosensor as a potential and affordable alternate of conventional methods like ELISA. The desirable LOD was recorded as 1 nU/mL. The repeatability and reproducibility were successfully inspected for ten repeated mensuration and the lowest RSD percentages were observed as about 5 % for the concentration of 1, 10 and 20 nU/mL. As a proof of the discussed results, the presented biosensor has a high sufficiency to be used in clinical laboratories to diagnose pancreatic cancer. We believe that our fabricated sensor can be the plan of diseases management program due to affordable rapid and label free detection of a targeted biomarkers.